Assessment of chlorine resistance in concrete in the tidal range and splash zone of a torrid marine region - Yu, Yongyan; Chen, Nan; Li, Lihui; Wang, Jian (Frontiers in Materials, 2023)
Based on China’s long-term goals for 2035, numerous projects are expected to be constructed in torrid marine regions, with increased chloride ion erosion, particularly in tidal and splash zones. To improve chlorine resistance performance, in this work, we proposed a method to assess the chlorine resistance of concrete in the tidal range and splash zones of a torrid marine region. To ensure consistency in assessment, an enhanced Fuzzy analytic hierarchy process (F-AHP) method was applied. 1) The factors that affected the chloride resistance of concrete in the tidal range and splash zones in torrid marine regions were theoretically analyzed. 2) The factors were classified into concrete material properties, concrete structure location, and marine organism impact, which have been insufficiently mentioned in previous chlorine resistance assessments and other protective measures. The weight of factors was calculated in an enhanced F-AHP method to ensure the consistency of judgment matrices from expert investigations. Membership functions were obtained based on engineering requirements, standards, and specifications to enhance their applicability to engineering. 3) The assessment was then applied to the marine concrete engineering of the Xiapu Bridge in Hainan Province, China, with apparent characteristics of a torrid marine environment. The methods for improving the chlorine resistance of concrete were subsequently proposed.